Analisa Kandungan Proksimat dan Serat Siomay Rumput Laut (Eucheuma Cottonii) Sebagai Camilan Sehat untuk Remaja Obesitas - Nathasa Weisdania Sihite; Manuntun Rotua (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The problem of obesity in adolescents is a common problem that often occurs in several regions in Indonesia. In 2018, it was informed that there was a 20% increase in the prevalence of obesity and overweight in adolescents. Seaweed has long been known to have high fiber content, the total fiber content is important for teenagers who want to lose weight like obese teenagers. Seaweed dumplings (siomay) are an alternative high-fiber snack for obese teenagers because it tastes good and is liked by all ages. The purpose of this research was to determine and analyze specifically the chemical content in the form of proximate and fiber analysis in seaweed siomay products. This research is experimental-based research with the experimental design used being a non-factorial Completely Randomized Design (CRD), chemical analysis was carried out at PT Saraswanti Indo Genetech Bogor. The results showed that seaweed dumplings (Eucheuma cottonii) can be used as a recommendation for healthy snacks that are high in fiber, with a contribution of 3-6 grams of fiber per serving. The results of the analysis also showed that the proximate content of seaweed dumplings per 100 grams contained water 61.48% (%ww), ash 1.39% (%bk), fat 0.79% (%bk), protein 4.48% (%bk), carbohydrates 31.86% ( %bk), 152.4 kcal of energy. The results of this analysis stated that the seaweed siomay in this study were following the standards by Standar Nasional Indonesia (SNI) for dumplings products.